Jedi Academy : return of the Padawan - Brown, Jeffrey, 1975- (New York, NY : Scholastic Inc., 2014)
Roan Novachez expected his second year at Jedi Academy to be a lot easier, but his star pilot training is tougher than he expected, his best friends start ignoring him, and the class bullies are trying to tempt him to the Dark Side, which looks like more fun to Roan.
School Library Journal, June 2014.
Booklist, May 2014.
Kirkus Review, June 2014.
4.2
3-6
GN670L
Keywords: School children -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Robots -- Juvenile fiction; Schools -- Juvenile fiction; Star Wars fiction; Children -- Fiction; Extraterrestrial beings -- Fiction; Robots -- Fiction; Schools -- Fiction; Star Wars fiction; Science fiction; Humorous stories; School children -- Fiction; Robots -- Fiction; School stories; Aliens (Fictional characters) -- Fiction; Middle schools -- Fiction; Humorous stories; Science fiction; Humorous fiction; Comics (Graphic works); Graphic novels